2020
DOI: 10.1002/fsn3.1831
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pomegranate peel extracts obtained using different solvents and their effects on cell cycle and apoptosis in leukemia cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
3
19
0
1
Order By: Relevance
“…The water extraction of pomegranate rind showed a remarkable extraction yield (1.3%) compared with those obtained by ethanol (0.8%) and acetone (0.2%) ( P < 0.05). The same results were demonstrated in previous studies (Abu‐Darwish et al., 2016; Tamborlin et al., 2020). Solvents with different polarities yield extracts with various chemical constituents and biological properties.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The water extraction of pomegranate rind showed a remarkable extraction yield (1.3%) compared with those obtained by ethanol (0.8%) and acetone (0.2%) ( P < 0.05). The same results were demonstrated in previous studies (Abu‐Darwish et al., 2016; Tamborlin et al., 2020). Solvents with different polarities yield extracts with various chemical constituents and biological properties.…”
Section: Resultssupporting
confidence: 91%
“…Qualitative analysis of bioactive compounds in the obtained extracts\fractions was performed using a liquid chromatographic system (LC‐8030, Shimadzu, Japan) consisting of degasser (DGU‐5A), quaternary solvent delivery pump (LC‐30 AD), auto‐sampler with cooler (S11‐30 AC), column temperature controller (CTO‐30A) and system controller (CBM‐20A). The sample was separated on an Agilent Zorbax Eclipse XDB‐C18 (150 mm length × 2.1 mm internal diameter, 3.5 μm film thickness) column with a mobile phase solution A (0.1% aqueous formic acid) and B (0.1% solution of formic acid in acetonitrile) (Tamborlin et al., 2020). Under the gradient elution condition, the mobile phase was eluted as follows: 5% solvent A for 5 min, 5–100% solvent B in 15 min and 100% solvent B for 5 min at a flow rate of 0.5 mL min −1 , after each run the column was washed and re‐equilibrated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies already reported other natural compound's effects on inducing PARP1 cleavage in cancer cells. Tamborlin et al (2020) showed cleavage of PARP1 and consequently apoptosis induction in leukemia cells (THP1) after the treatment for 48 hr with a combination of ellagic acid and punicalagin (Tamborlin et al, 2020). Lin et al (2015) treated MCF‐7 cells with 43 μM of luteolin and 30 μM of apigenin for 24 hr, and also observed the PARP1 cleavage in both treatments (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Punicalagin has been shown to possess anti-leukemic activities by suppressing proliferation and promoting apoptosis of HL-60 leukemic cells through caspase-3 activation (Chen et al, 2009). Pomegranate juice and peel extracts contain punicalagin, which is responsible for the induction of apoptosis, S phase cell cycle arrest, and inhibiting proliferation in CCRF-CEM, MOLT-3, HL-60 and THP-1 cells (Dahlawi et al, 2013;Tamborlin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%